Putting a Face on It Individual Exposure and Subjectivity in Journalism - Kjos Fonn, Birgitte; Hyde-Clark, Nathalie; Benestad Hågvar, Yngve; Hornmoen, Harald (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
"Putting a Face on It analyses and discusses how subjectivity and exposure of individuals now affect most journalistic topics and genres: from politics to sports journalism, from science journalism to journalism about terrorism. Individual exposure and subjectivity affect news and features, photos and front pages, and are at the core of an increasing dialogue with digital media users. One aim of this book is therefore to present some of this variation. Another is to contribute to the discourse about the present state of journalism and where it is heading. Putting a Face on It will appeal to researchers, teachers, students, writers, journalists and other media-interested readers."